School Literacy Culture Cultivates Reading Interest in Primary Students: Budaya Literasi Sekolah Menumbuhkan Minat Membaca pada Siswa Sekolah Dasar - Rizka Marela Nasir; Ahmad Nurefendi Fradana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Low reading engagement among primary school learners remains a persistent educational concern, as reading underpins academic success and lifelong learning. Specific Background: Literacy culture in schools extends beyond basic reading and writing to include accessing, interpreting, and producing information, supported by structured activities such as classroom reading corners and routine reading sessions. Knowledge Gap: Despite widespread literacy initiatives, there is limited phenomenological evidence describing how school-based literacy culture is experienced by stakeholders and how it relates to students’ reading interest. Aims: This study aimed to describe the implementation of literacy culture in fostering reading interest among primary school students. Results: Using a qualitative phenomenological approach involving principals, teachers, and third-grade students, findings indicate that literacy culture manifests through three stages—habituation, development, and learning—supported by daily shared reading activities lasting approximately 10–15 minutes and the provision of attractive reading corners and relevant books. These practices were associated with observable enthusiasm, routine reading behavior, and increased participation in literacy activities. Novelty: The study offers an experiential account of literacy culture implementation within a classroom context, highlighting the integration of environmental design, habitual practice, and instructional support. Implications: Establishing consistent literacy routines and accessible reading environments may support sustained student engagement with texts and contribute to broader educational quality improvement in primary schools. Highlights: Structured stages of literacy practice shape sustained student reading habits. Daily shared reading sessions generate observable enthusiasm toward texts. Accessible classroom book spaces encourage voluntary engagement with printed materials. Keywords: Literacy Culture; Reading Interest; Primary Education; Reading Corner; Phenomenological Study